2014
DOI: 10.1016/j.celrep.2014.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Somatically Acquired Amplifications and Deletions in Apparently Normal Tissues of Ovarian Cancer Patients

Abstract: Little is understood about the occurrence of somatic genomic alterations in normal tissues, and their significance in the context of diseases. Here we identified potential somatic copy number alterations (pSCNA) in apparently normal ovarian tissue and peripheral blood of 423 ovarian cancer patients. There were on average 2–4 pSCNAs per sample detectable at a tissue-level resolution, although some individuals had orders of magnitude more. Accordingly, we estimated the lower bound of the rate of pSCNAs per cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…In general, the proportion of CNAs that were ubiquitous was smaller than the corresponding proportion of SNVs. This is in line with observations that as much as half of the somatic mutations in tumor genomes likely arise in benign progenitor cell prior to tumor development (and thus are ubiquitous) (Tomasetti et al, 2013), while copy number alterations in pre-neoplastic tissues are rare (Aghili et al, 2014;De, 2011). Occasional genome doubling in non-small cell lung cancer has been reported (Jamal-Hanjani et al, 2017), but we found no evidence for genome doubling in our samples based on allele-specific copy number profiles.…”
Section: Landscape Of Genomic Changes In the Tumor Samplessupporting
confidence: 92%
“…In general, the proportion of CNAs that were ubiquitous was smaller than the corresponding proportion of SNVs. This is in line with observations that as much as half of the somatic mutations in tumor genomes likely arise in benign progenitor cell prior to tumor development (and thus are ubiquitous) (Tomasetti et al, 2013), while copy number alterations in pre-neoplastic tissues are rare (Aghili et al, 2014;De, 2011). Occasional genome doubling in non-small cell lung cancer has been reported (Jamal-Hanjani et al, 2017), but we found no evidence for genome doubling in our samples based on allele-specific copy number profiles.…”
Section: Landscape Of Genomic Changes In the Tumor Samplessupporting
confidence: 92%
“…There is literature (3034) that supports evidence of abnormal mutations in normal-appearing tissues in other organs including skin, lung, and ovaries. Regions that harbor abnormal mutations may presage organizational changes on the molecular level that are not yet discernable via conventional light microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In a postreproductive microenvironment deviating from the evolved one, the balance shifts from stabilizing to positive selection, and thus, irrespective of life span, this aging-induced change should trigger somatic evolution driven by previously accumulated mutations. The exponentially increasing clonality shown to develop during human postreproductive ages in the hematopoietic system (47,48,50,51,67), in fact, provides a strong line of evidence that the balance between stabilizing and positive selection changes in SCs pools in an age-dependent manner in normal tissues, irrespective of carcinogenesis. It also supports the idea that the selective value of oncogenic mutations should change (increase) with age.…”
Section: Discussionmentioning
confidence: 99%
“…3, the character of selection should thus have a far greater effect on the odds of multidriver cancers than the mutation rate by exponentially increasing the number of dividing cells, and thus the total number of cell divisions within a proliferating clone [D(t) in Eq. 3] by a certain time t. Evidence for the effects of generally increased positive selection on cancer risk comes from the above-mentioned studies that reveal a greater risk for hematopoietic malignancies in aged people with clonal hematopoiesis (47,48,50,51,67). Increased clonality in HSC pools is expected to result from clonal expansions driven by positive selection.…”
Section: Sc Divisions and The Odds Of Accumulating Multiple Oncogenicmentioning
confidence: 99%